Timing of Cord Clamping and it’s Effect on Haematocrit and Clinical Outcome of Neonate - Mitra, Ujjal; Shahidullah, Md; Mannan, Abdul; Nahar, Zakia; Dey, Sanjoy Kumar; Mannan, Istiaq (Bangladesh Journal of Child Health, 2010)
Background: It is the usual practice to clamp umbilical cord immediately after birth. There is no sound evidence to support this approach, which might deprive the newborn of some benefits, such an increase in iron storage. Objectives: The study was done to determine the effect of timing of cord clamping on neonatal venous haemoglobin and haematocrit values and clinical outcome within neonatal period. Methodology: This was a randomized, controlled trial performed in Obstetrical Unit with support of Neonatal Unit of Paediatrics and Department of Clinical Pathology of BSMMU on neonates born at term without complication to mothers with uneventful pregnancies. After obtaining written parental consent newborns were randomly assigned to cord clamping within first 15 seconds (group-I Early Cord Clamping, ECC), at around 1 minute (group-II Late Cord Clamping, LCC) after birth. The infant's venous haemoglobin and haematocrit values were measured at 6 hours and 24 to 48 hours after birth. Results: 130 mothers were selected for study purpose. Finally 98 were analyzed, 50 in early cord clamping group and 48 in late cord clamping group. Mean venous haemoglobin and haematocrit values at around 6 and 24 to 48 hours of life were measured. Results were within physiological limit but difference were significant between 2 study groups. The prevalence of anaemia (Hb <14 gm%) was not significantly higher in group-I than group-II but relatively more newborns were anaemic in group-I. There was no significant difference in other neonatal outcomes and maternal postpartum events. Conclusions: Delayed cord clamping at birth increases neonatal venous haemoglobin and haematocrit values within a physiologic range. No harmful effects were observed among both groups. Furthermore this intervention seems to reduce the incidence of neonatal anemia. This practice has been shown to be safe and should be practiced to increase neonatal haemoglobin and haematocrit values at birth. Key words: Early cord clamping (ECC); late cord clamping (LCC). DOI: 10.3329/bjch.v33i1.5670 Bangladesh Journal of Child Health 2009; Vol.33(1): 16-21